A study on hedges in conversations in english and vietnamese films. - Lê,Thị Kim Tuyến (đhnn, 2016)
This thesis was done in an effort to investigate hedges in conversations in English and Vietnamese films. The research was carried out in the hope to clarify the manifestation and pragmatic features of hedges in conversations in English and Vietnamese films; find out the similarities and differences in the use of hedges in conversations in films between the two languages. To achieve the purposes, a combination of research methods including descriptive method, qualitative method and quantitative method was used. As regards the data for the research, a total of 194 hedges were collected from 700 utterances spoken by characters in conversations in three TV films series in English and in Vietnamese. The result showed that in terms of the manifestation, hedges in English and Vietnamese could be in forms of words, phrases, clauses and sentences. The words as hedges were more frequently used and the sentences as hedges were used less frequently than others. In terms of the pragmatic features, both English speakers and the Vietnamese ones used hedges to show their respect to the CP and to the politeness. The research also provided some implications for teaching and learning hedges in English, which are useful for Vietnamese learners of English to be successful in cross-cultural communication.
Keywords: study on hedges,conversations, english vietnamese films -- conversations -- english vietnamese films